Impact of delay between imaging and treatment in patients with potentially curable pancreatic cancer. Issue 3 (17th November 2015) - Sanjeevi, S.; Ivanics, T.; Lundell, L.; Kartalis, N.; Andrén‐Sandberg, Å.; Blomberg, J.; Del Chiaro, M.; Ansorge, C.
Abstract : Background: Locoregional pancreatic ductal adenocarcinoma (PDAC) may progress rapidly and/or disseminate despite having an early stage at diagnostic imaging. A prolonged interval from imaging to resection might represent a risk factor for encountering tumour progression at laparotomy. The aim of this study was to determine the therapeutic window for timely surgical intervention. Methods: This observational cohort study included patients with histologically confirmed PDAC scheduled for resection with curative intent from 2008 to 2014. The impact of imaging‐to‐resection/reassessment (IR) interval, vascular involvement and tumour size on local tumour progression or presence of metastases at reimaging or laparotomy was evaluated using univariable and multivariable regression. Risk estimates were approximated using hazard ratios (HRs). Results: Median IR interval was 42 days. Of 349 patients scheduled for resection, 82 had unresectable disease (resectability rate 76·5 per cent). The unresectability rate was zero when the IR interval was 22 days or shorter, and was lower for an IR interval of 32 days or less compared with longer waiting times (13 versus 26·2 per cent; HR 0·42, P = 0·021). It was also lower for tumours smaller than 30 mm than for larger tumours (13·9 versus 32·5 per cent; HR 0·34, P < 0·001). Tumours with no or minor vascular involvement showed decreased rates of unresectable disease (20·6 per cent versus 38 per cent when there was major or combined vascular involvement; HR 0·43, P = 0·007). However, this failed to reach statistical significance on multivariable analysis ( P = 0·411), in contrast to IR interval ( P = 0·028) and tumour size ( P < 0·001). Conclusion: Operation within 32 days of diagnostic imaging reduced the risk of tumour progression to unresectable disease by half compared with a longer waiting time. The results of this study highlight the importance of efficient clinical PDAC management. Abstract : The earlier the better